Adhesion Properties Of Ultraviolet-Cured Rubber Based Adhesives By Benzoyl Peroxide As Sole Initiator - Goon, Shuang Er (2024)
UV initiators are generally more expensive than conventional free radical initiator. Furthermore, combining UV initiator with conventional free radical initiator may induce initiation complication. Thus, there is a need to assess conventional free radical initiator such as benzoyl peroxide as sole UV-initiator to initiate crosslinking in UV-cured rubber-based adhesive. This study is significant since it addresses another characteristic of benzoyl peroxide as sole UV-initiator in contrast with its common role as thermal catalyst. This study will contribute to the existing literature by examining the adhesion properties of UV-cured rubber based adhesives by benzoyl peroxide as sole initiator. Parameters analysed were number of UV passes (0, 5, 10, 15, 20), coating thickness (60 μm and 120 μm) and type of rubber (SMR-L, ENR-25, ENR-50). The first objective is to assess the abilities of benzoyl peroxide as sole UV-initiator to initiate crosslinking in rubber-based adhesive as evaluated by viscosity measurement, gel content test, FTIR and pendulum hardness.